Lysyl-tRNA synthetase gene of Campylobacter jejuni. - Chan, V L (1992)
We report the cloning and complete nucleotide sequence of the Campylobacter jejuni lysyl-tRNA synthetase gene (lysS). The C. jejuni lysS gene sequence shows high homology to the two Escherichia coli lysyl-tRNA synthetase genes, lysS and lysU. The Campylobacter lysyl-tRNA synthetase protein (LysRS) shows 47.9 and 46.6% sequence identity to the E. coli enzymes encoded by the lysS and lysU genes, respectively. The LysRS encoded by the C. jejuni gene is a polypeptide of 501 amino acids with a deduced molecular weight of 57,867. The enzyme is active in E. coli. The gene is expressed from its own promoter, and the transcription start site has been mapped. The carboxyl-terminal codon of the C. jejuni lysS gene overlaps by 1 bp with the Met initiation codon of the glyA gene, which has been shown to have a promoter which is functional in E. coli (V.L. Chan and H.L. Bingham, Gene 101:51-58, 1991). C. jejuni, unlike E. coli, has only one lysyl-tRNA synthetase gene.